2017
DOI: 10.1111/1742-6723.12842
|View full text |Cite
|
Sign up to set email alerts
|

Adolescent presentations to an adult hospital emergency department

Abstract: Contrary to reported staff perceptions, adolescent chronic physical illness presentations were not a major burden. Alcohol was likely under-recorded as a contributing factor to presentations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 19 publications
(37 reference statements)
0
4
0
Order By: Relevance
“…Adolescents prefer to present as walk-in patients [ 21 ] and do so conspicuously often during the weekends [ 20 ]; this has also been observed in other studies. The most frequent triages in a study conducted in an Australian ED were—similar to our patients’ collective—semi-urgent (4/5) and non-urgent (5/5) [ 20 ]. Our data showed that there was a protective association with surgical treatment for walk-in patients.…”
Section: Discussionmentioning
confidence: 55%
See 1 more Smart Citation
“…Adolescents prefer to present as walk-in patients [ 21 ] and do so conspicuously often during the weekends [ 20 ]; this has also been observed in other studies. The most frequent triages in a study conducted in an Australian ED were—similar to our patients’ collective—semi-urgent (4/5) and non-urgent (5/5) [ 20 ]. Our data showed that there was a protective association with surgical treatment for walk-in patients.…”
Section: Discussionmentioning
confidence: 55%
“…Several ED studies, including our initial study, found that injuries were the most common cause of adolescent presentations to the ED [ 11 , 20 22 ]. Furthermore, studies have shown that in the age group of adolescents, males (52–60%) present to the ED more often than females [ 6 , 7 , 20 , 21 , 23 , 24 ]. For the subgroup of presentations due to trauma, this difference is even greater.…”
Section: Discussionmentioning
confidence: 99%
“…This finding aligns with specific study of paediatric ED utilisation in Melbourne during the first wave. 6 Adolescents aged 14–18 most commonly present to ED due to injuries, 22 and online supplemental figure 2 depicts a substantial reduction in injury presentation for those aged <18, and 18–40, during both waves. Observed reductions among young adults may reflect fewer road accidents and/or alcohol-related injuries (including violence and falls).…”
Section: Discussionmentioning
confidence: 99%
“…This is the first Australian study to explore adult ED clinician perspectives regarding AYA presentations. Most clinicians lacked specific adolescent health training and overestimated the actual burden of AYA chronic physical illness in EDs based on retrospective data 4 suggesting that such presentations are more memorable than prevalent.…”
Section: Transition Care and The Emergency Departmentmentioning
confidence: 99%